Sistem Keamanan Peternakan Ayam Petelur Menggunakan Sumber Daya Panel Surya - Sabriansyah, Dandi; ., Muhajir (MDP Student Conference, 2026)
The security of laying hen farms in remote areas without access to PLN electricity remains a major problem due to the high risk of theft and predation. This study designs a solar energy-based security system for laying hen farms in areas without access to PLN electricity. The system integrates a laser sensor - LDR as an intrusion detector, Arduino Nano as a controller, ESP32-CAM for visual monitoring, and a buzzer as an alarm, with a 20 WP solar panel power supply and a 12 V 10 Ah battery. An event-driven approach is applied to activate the camera and alarm only when a disturbance occurs. The test results show a 100% detection success rate with an average response time of 0.38 seconds and a false positive rate of less than 2%. The system's power consumption is 0.52 W in standby mode and 2.2 W at peak load, with a daily energy requirement of approximately 25.3 Wh that can be met by the solar panel. This system is effective and feasible to be implemented in small to medium-scale laying hen farms in remote areas.